Relationship of DNA double-strand breaks to synapsis in Drosophila. - Jang, J.K.; Sherizen, D.E.; Bhagat, R.; Manheim, E.A.; McKim, K.S. (Journal of Cell Science, 2003)
The relationship between synaptonemal complex formation (synapsis) and double-strand break formation (recombination initiation) differs between organisms. Although double-strand break creation is required for normal synapsis in Saccharomyces cerevisiae and the mouse, it is not necessary for synapsis in Drosophila and Caenorhabditis elegans. To investigate the timing of and requirements for double-strand break formation during Drosophila meiosis, we used an antibody that recognizes a histone modification at double-strand break sites, phosphorylation of HIS2AV (gamma-HIS2AV). Our results support the hypothesis that double-strand break formation occurs after synapsis. Interestingly, we detected a low (10-25% of wildtype) number of gamma-HIS2AV foci in c(3)G mutants, which fail to assemble synaptonemal complex, suggesting that there may be both synaptonemal complex-dependent and synaptonemal complex-independent mechanisms for generating double-strand breaks. Furthermore, mutations in Drosophila Rad54 (okr) and Rad51 (spnB) homologs cause delayed and prolonged gamma-HIS2AV staining, suggesting that double-strand break repair is delayed but not eliminated in these mutants. There may also be an interaction between the recruitment of repair proteins and phosphorylation.